Cigarette smoke exposure reduces hemorrhagic shock induced circulatory dysfunction in mice with attenuated glucocorticoid receptor function - Wepler, Martin; Preuss, Jonathan M.; Tilp, Cornelia; Keck, Martina; Blender, Jochen; Wachter, Ulrich; Merz, Tamara; Vogt, Josef; Kress, Sandra; Gröger, Michael; Hoffmann, Andrea; Fink, Marina; et al. (Frontiers in Immunology, 2022)
Introduction: We previously showed that attenuated glucocorticoid receptor (GR) function in mice (GRdim/dim) aggravates systemic hypotension and impairs organ function during endotoxic shock. Hemorrhagic shock (HS) causes impaired organ perfusion, which leads to tissue hypoxia and inflammation with risk of organ failure. Lung co-morbidities like chronic obstructive pulmonary disease (COPD) can aggravate tissue hypoxia via alveolar hypoxia. The most common cause for COPD is cigarette smoke (CS) exposure. Therefore, we hypothesized that affecting GR function in mice (GRdim/dim) and pre-traumatic CS exposure would further impair hemodynamic stability and organ function after HS. Methods: After 3 weeks of CS exposure, anesthetized and mechanically ventilated GRdim/dim and GR+/+ mice underwent pressure-controlled HS for 1h via blood withdrawal (mean arterial pressure 35mmHg), followed by 4h of resuscitation with re-transfusion of shed blood, colloid fluid infusion and, if necessary, continuous intravenous norepinephrine. Acid–base status and organ function were assessed together with metabolic pathways. Blood and organs were collected at the end of the experiment for analysis of cytokines, corticosterone level, and mitochondrial respiratory capacity. Data is presented as median and interquartile range. Results: Nor CS exposure neither attenuated GR function affected survival. Non-CS GRdim/dim mice had a higher need of norepinephrine to keep target hemodynamics compared to GR+/+ mice. In contrast, after CS exposure norepinephrine need did not differ significantly between GRdim/dim and GR+/+ mice. Non-CS GRdim/dim mice presented with a lower pH and increased blood lactate levels compared to GR+/+ mice, but not CS exposed mice. Also, higher plasma concentrations of some pro-inflammatory cytokines were observed in non-CS GRdim/dim compared to GR+/+ mice, but not in the CS group. With regards to metabolic measurements, CS exposure led to an increased lipolysis in GRdim/dim compared to GR+/+ mice, but not in non-CS exposed animals. Conclusion: Whether less metabolic acidosis or increased lipolysis is the reason or the consequence for the trend towards lower catecholamine need in CS exposed GRdim/dim mice warrants further investigation.